О БОЛЕСТИМА ЈУНАКА НАРОДНИХ ПЈЕСАМА (Philological Studies, 2019)
This paper discusses diseases and the hero’s illness in oral poetry, their variations related to the level of themes and motifs, the pragmatic aspects of ballads, the shaping and the reception of the disease and healing motifs, developing their semantic and syuzhet potential to the maximum within the boundaries of this genre. The literary organization of the disease experience, fear of death and the hope of healing is viewed within an interdisciplinary approach, in an area determined by medicine and art. The author interprets models and motifs that can be associated with folk medicine and magical practices of mediation between disease and healing, i.e. superstitions that include demons of illness and those who know the secret of healing. The material consists of folk poems recorded in the 19th and 20th century in Bosnia and Herzegovina, some from Novica Šaulić’s collection of poems and some from the anthology collections of Vuk Karadžić and Nikola Andrić; despite different ethnic connotations, they are often related due to the same cultural and geographical space.
Keywords: folk ballads, illness, healing, magic, metaphor